Social interaction skills and playing with blind or low vision children in school context - Silva, Lucas de Paiva (2020)
The aim of this study was to analyze the skills of social interaction and the playing of children with blindness or low vision in a school context, in the perception of their respective teachers of the regular class. This is a quantitative, descriptive, analytical and cross-sectional research carried out from April to July 2019. Sixteen teachers participated, accompanying 18 children with blindness or low vision, enrolled in schools of the Municipal Education Network, in the Early Years of Elementary Education, from the Metropolitan Region of Recife/PE. The School Function Assessment instrument was used for data collection. To compare the percentages of the levels of the factors evaluated, the Chi-square test was applied to compare proportions. To assess the level of assistance demanded by the students, the median statistics and interquartile range of the assessed tasks were calculated. The results showed that children with blindness or low vision had greater difficulty in playing activities. As for social participation, it was observed that the same children developed basic and sufficient social interaction skills for living in a school environment. The comparison of the tasks of social interaction and playing identified, according to the teachers' perception, that the performance in playing is more impaired in children with visual impairment, as well as needing greater adaptations and assistance.